Alterations of cell-mediated immune response in children with febrile seizures - Montelli, Terezinha C.B. [UNESP]; Soares, Angela M.V.C.; Parise-Fortes, Maria R.; Rezkallah-Iwasso, Maria T.; Padula, Niura M.R.; Peraçoli, Maria Terezinha S. (FapUNIFESP (SciELO), 1997)
The aim of the present investigation was to study the distribution of T-cell subsets in peripheral blood defined by monoclonal antibodies and by the lymphocyte proliferative response to phytohemagglutinin (PHA) in 30 children with febrile seizures and in 14 age-matched control subjects. Frequent respiratory, urinary and dermatologic infections were observed in 22 patients. The immunologic parameters showed that 64% of the patients presented an increased number of CD8+ cells and a low helper/suppressor ratio was observed in 60% of the patients. In addition, the proliferative response of lymphocytes to PHA was impaired in the patients It was observed the presence of inhibitory activity on lymphocyte function in the plasma of 33% of children with febrile seizures. These results suggest that patients with febrile seizures have an impairment of cellular immunity that may be connected with this epileptic syndrome and explain the infections observed.
Keywords: Febrile seizures; Infections; Lymphocyte proliferative response; T cell subsets; diagnostic agent; immunoglobulin G; phytohemagglutinin; phytohemagglutinin P; phytohemagglutinin-P; blood; CD4 CD8 ratio; febrile convulsion; female; follow up; human; immunology; infant; male; preschool child; prospective study; T lymphocyte subpopulation; CD4-CD8 Ratio; Child, Preschool; Female; Follow-Up Studies; Humans; Immunoglobulin G; Infant; Male; Phytohemagglutinins; Prospective Studies; Seizures, Febrile; T-Lymphocyte Subsets